Odelouca Dam Construction: Numerical Analysis - Brito, A. (2012)
Odelouca dam is an embankment dam, with 76 m height, recently constructed in the south of Portugal. It is zoned with a core consisting of colluvial and residual schist soil and with soil-rockfill mixtures making up the shells (weathered schist with a significant fraction of coarse sized particles). This paper presents a numerical analysis of Odelouca Dam`s construction. The material con-stants of the soil model used are determined from a comprehensive testing programme carried out in the Civil Engineering National Laboratory (LNEC) during the dam construction for the hydraulic and mechanical characterization of the materials used. Computational results are then compared between to the ones obtained from the dam monitoring system during the construction stage.